Translocator protein as a biomarker in head and neck cancer - Tuominen, Sanni (fi=Turun yliopisto|en=University of Turku|, 2025)
Head and neck squamous cell carcinoma (HNSCC) consists of heterogeneous tumours originating from the head and neck region. Although advances in the treatment of HNSCC have been made during the last decade, cancer recurrence and treatment resistance remain challenges in HNSCC. Currently, human papilloma virus (HPV), and its surrogate marker p16 for oropharyngeal cancer and Epstein–Barr virus (EBV) for nasopharyngeal cancer are the only biomarkers widely used in clinics. Thus, there is an urgent need for biomarkers to predict the prognosis and treatment response of HNSCC. Translocator protein (TSPO) is a small protein located on the outer mitochondrial membrane. It has been suggested that it participates in several cellular functions, but its exact role remains unclear. Studies have shown an association between high TSPO expression and worse prognosis in several types of cancer. The aim of this thesis was to evaluate the prognostic and predictive potential of TSPO in HNSCC. TSPO expression was determined in a large population-based tissue microarray (TMA) and The Cancer Genome Atlas (TCGA) patient cohorts, and possible associations with clinicopathological information were analysed. In addition, the role of TSPO in oxidative metabolism and DNA damage response was studied in HNSCC cells. Finally, the specificity of the TSPO-PET tracer [18F]F-DPA was evaluated in HNSCC xenografts and cell lines. Lower TSPO tumour expression was associated with worse survival in HNSCC, particularly in patients with p16-positive oropharyngeal cancer. Furthermore, lower TSPO expression was associated with worse survival in patients receiving radiotherapy. Low TSPO expression was associated with reduced mitochondrial respiration and DNA damage response in FaDu cells. The [18F]F-DPA uptake was specific in HNSCC xenografts and cells and increased after radiotherapy. The results of this thesis indicate that TSPO can be used as a prognostic biomarker of HNSCC and, mechanistically, may participate in the radiotherapy-induced DNA damage response via the regulation of oxidative phosphorylation. Further investigation in the usability of TSPO-PET imaging for predicting radiotherapy response and clinical value of the association between low TSPO expression and worse outcomes in p16-positive oropharyngeal cancer are warranted.

Translokaattoriproteiini biomarkkerina pään ja kaulan alueen syövissä Pään ja kaulan alueen levyepiteelisyövät ovat heterogeeninen joukko pään ja kaulan alueen kasvaimia. Vaikka kyseisten kasvainten hoidot ovat kehittyneet viimeisen vuosikymmenen aikana, syövän uusiutuminen ja hoitoresistenssi ovat yhä haasteita. Ihmisen papilloomavirus ja sen korvike p16 suunielun syövissä ja Epstein-Barr virus nenänielun syövissä ovat ainoat biomarkkerit, joita käytetään laajasti eri klinikoissa. Uusien biomarkkerien löytäminen pään ja kaulan alueen syöpien ennusteen ja hoitovasteen arvioimiseen onkin ensiarvoisen tärkeää. Translokaattoriproteiini (TSPO) on mitokondrion ulkokalvolla sijaitseva proteiini, jonka on ehdotettu osallistuvan moniin solun toimintoihin. TSPOn korkean ilmentymisen on osoitettu liittyvän potilaan huonoon ennusteeseen useissa syövissä. Tässä väitöskirjassa tutkittiin TSPOn kykyä toimia ennusteellisena biomarkkerina pään ja kaulan alueen syövissä väestöpohjaista kudosmikrosirua ja TCGAn potilaskohorttia käyttäen. Lisäksi tutkittiin TSPOn toiminnallista roolia oksidatiivisen fosforylaation ja DNA-vauriovasteen säätelyssä pään ja kaulan alueen syöpäsoluissa. Lopuksi määritettiin TSPO-PET merkkiaineen, [18F]F-DPAn, spesifisyys pään ja kaulan alueen kokeellisissa kasvaimissa ja soluissa. Matalampi TSPOn ilmentyminen liittyi potilaan huonompaan ennusteeseen etenkin p16-positiivisisa suunielun syövissä. Lisäksi matala TSPOn ilmentyminen liittyi huonompaan ennusteeseen pelkästään sädehoidetuilla potilailla. Matala TSPOn ilmentyminen liittyi matalampaan oksidatiiviseen aineenvaihduntaan ja DNA-vaurion vasteeseen. [18F]F-DPAn kertymä oli spesifistä pään ja kaulan alueen syöpien kokeellisissa kasvaimissa ja soluissa ja kertymä nousi sädehoidon jälkeen. Tutkimuksen tulokset osoittavat, että TSPOlla on potentiaalia toimia ennusteellisena biomarkkerina pään ja kaulan alueen syövissä. TSPO saattaa säädellä sädehoidon aiheuttamaa DNA-vauriovastetta oksidatiivisen fosforylaation säätelyn välityksellä. Sädehoitovasteen ennustaminen PET-kuvantamisella TSPO-merkkiainetta hyödyntäen vaatii lisätutkimuksia. TSPOn yhteys huonompaan ennusteeseen p16-positiivisissa suunielun syövissä saattaa olla kliinisesti merkitsevä löydös ja vaatii jatkotutkimuksia.